Asociatividad y comercialización efectiva en pequeños productores de aguacate en Colombia con un enfoque de valor compartido, a través de la implementación de un modelo de innovación social. - García Murcia, Julián Fabrizzio (Universidad Antonio Nariño, 2023)
The avocado is the fifth most important tropical fruit in the world and its consumption has increased especially in countries such as the United States, France, Germany and Spain; This fruit sustains its high demand in the world market thanks to its characteristics, such as its flavor, its nutritional qualities, and its wide possibilities of use, both culinary and in the pharmaceutical and cosmetic industries (Banco de la República, 2012).